Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Answer:
- h(x + 3) - 5
Step-by-step explanation:
Given function h(x).
Shift left:
- h(x) → h(x + 3)
Shift down:
- h(x + 3) → h(x + 3) - 5
Given function is,
→ h(x)
As we shift left,
→ h(x) = h(x + 3)
As we shift down,
→ h(x + 3) = h(x+3)-5
Then the equation is,
→ h(x+3)-5
It is correct answer.
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.